Assessing the dendroclimatic potential of Nothofagus betuloides (Magellan's beech) forests in the southernmost Chilean Patagonia - Fuentes, Mauricio; Aravena Donaire, Juan Carlos; Seim, Andrea; Linderholm, Hans W. (My University, 2019)
Key messageTree growth of Nothofagus betuloides forests south of 50 degrees S is affected by local temperature and precipitation together with large-scale high-latitude climate patterns, but also significant influences from the Tropical Pacific were found.The characterization of past climate dynamics in southern South America is difficult due to the shortness of instrumental data. However, abundant forests in the southernmost part of the continent makes it an ideal place to assess the dendroclimatological potential for developing high-resolution climate proxy time series to extend the observations back in time. Whereas the majority of dendroclimatological studies have focused on latitudes north of 50 degrees S, we present six new Magellan's beech (Nothofagus betuloides (Mirb.) Oerst.) tree-ring width (TRW) chronologies, spanning between 202 and 500years, developed from southernmost Patagonia (>50 degrees S), Chile. The climate signal in the trees was analyzed using local station data, regional sea surface temperature (SST) and large-scale atmospheric indices: the Southern Oscillation Index (SOI) and the southern annual mode (SAM). The correlations between individual site chronologies and observed summer temperatures and precipitation varied, reflecting diverse microsite conditions and local scale geographic patterns. An influence of southern Pacific SST was evident at two of the northern sites. Although the associations with SOI and SAM were weak, the influence of regional sea level pressure on tree growth in the region was evident.
Keywords: tree rings; nothofagus betuloides; climate signal; sam; soi; sst; slp; south pacific